Tren Penggunaan Antikoagulan Oral Direk dan Warfarin pada Pasien Fibrilasi Atrium - Musnelina, Lili; Handayani, Fitri; Hoa Vo, Thanh -; Pontoan, Jenny (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Treatments used in atrial fibrillation therapy, such as those of anticoagulants, consist of vitamin K antagonists (warfarin) and direct oral anticoagulants (dabigatran, apixaban, rivaroxaban, and edoxaban). The use of warfarin requires regular monitoring of prothrombin time (PT) and international normalised ratio (INR). The therapeutic dose range is narrow, but the price is cheaper. Oral anticoagulants are directed, the incidence of major bleeding is lower, ease of use, food and drug interactions are minor, the half-life is shorter, and there is a lack of laboratory monitoring needs. Based on this problem, researchers conducted a study to determine the trend of using warfarin and oral anticoagulants in patients with atrial fibrillation at a public hospital in Jakarta. This study uses a qualitative approach, with longitudinal methods and retrospective data using outpatient medical records for the period 2014 to 2018. The trend of using warfarin anticoagulants decreased from 82.3% in 2014 to 62% in 2016, while oral anticoagulants were reduced. Direct oral anticoagulants are rivaroxaban and dabigatran, which are more widely used than apixaban, and edoxaban; no data on their use has been obtained. The opposite was true from 2017 to 2018, when the use of warfarin increased and caused a decrease in the use of direct oral anticoagulants. This research is expected to contribute to various parties, both health practitioners and academics, in terms of selecting therapies for atrial fibrillation.